2022
DOI: 10.1111/all.15301
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and treatment of patients with Chronic rhinosinusitis with nasal polyps in Germany—A claims data study

Abstract: Background There are different levels of severity among patients who suffer from chronic rhinosinusitis with nasal polyps (CRSwNP). In this study, the epidemiology of CRSwNP and severe CRswNP was estimated. Methods A retrospective claim data analysis was conducted on adult CRSwNP patients (ICD‐10: J33), and those classified as severe CRSwNP patients with inadequate disease control (based upon combinations of previous and current treatments) between 2015 and 2019. Prevalence and incidence figures were calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
1
5
0
1
Order By: Relevance
“…11 Another study in Germany demonstrated a higher prevalence of CRSwNP in men (approximately 7,200 individual per million) than women (approximately 4,700 individual per million) over five years. 12 Exposure to tobacco smoke plays an active role in increasing chronic rhinosinusitis because it can trigger mucosal changes and damage to nasal cilia and paranasal sinuses. 13 However, an epidemiological study by Ference et al in 2015 stated that the incidence of CRS in women was elevated two times than in men because of hormonal factors.…”
Section: Discussionmentioning
confidence: 99%
“…11 Another study in Germany demonstrated a higher prevalence of CRSwNP in men (approximately 7,200 individual per million) than women (approximately 4,700 individual per million) over five years. 12 Exposure to tobacco smoke plays an active role in increasing chronic rhinosinusitis because it can trigger mucosal changes and damage to nasal cilia and paranasal sinuses. 13 However, an epidemiological study by Ference et al in 2015 stated that the incidence of CRS in women was elevated two times than in men because of hormonal factors.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate the population eligible for treatment, the prevalence of CRSwNP [22,23] was applied to the Italian adult population residents in 2022 (ISTAT, 2023). Therefore, a funnel of inclusion criteria was applied, estimating the number of Italian patients with severe CRSwNP for whom standards of care were not effective.…”
Section: Target Populationmentioning
confidence: 99%
“…Die CRS ist durch das persistierende Vorliegen von 2 der 4 Kardinalsymptome Nasenatmungsbehinderung, Riechstörung, Gesichtsschmerzen oder Rhinorrhoe über eine minimale Krankheitsdauer von 12 Wochen definiert. Zusätzlich unterscheidet sich die CRS phänotypisch hinsichtlich des Vorliegens nasaler Polypen in die Gruppe mit Polypen (20-30 %, CRSwNP) und ohne Polypen (CRSsNP) [4]. Die Diagnose von Polypen sollte dabei regelhaft endoskopisch gesichert werden [5].…”
Section: Introductionunclassified